Advances in Atomic Force Microscopy: Imaging of Two- and Three-Dimensional Interfacial Water - Cao, Duanyun; Song, Yizhi; Tang, BinZe; Xu, Limei (Frontiers in Chemistry, 2021)
Interfacial water is closely related to many core scientific and technological issues, covering a broad range of fields, such as material science, geochemistry, electrochemistry and biology. The understanding of the structure and dynamics of interfacial water is the basis of dealing with a series of issues in science and technology. In recent years, atomic force microscopy (AFM) with ultrahigh resolution has become a very powerful option for the understanding of the complex structural and dynamic properties of interfacial water on solid surfaces. In this perspective, we provide an overview of the application of AFM in the study of two dimensional (2D) or three dimensional (3D) interfacial water, and present the prospect and challenges of the AFM-related techniques in experiments and simulations, in order to gain a better understanding of the physicochemical properties of interfacial water.